A systematic review of men's experiences of their partner's mastectomy: coping with altered bodies. Issue 9 (7th May 2014) - Rowland, Emma; Metcalfe, Alison
Abstract Objective To explore men's experiences of their partner's altered physique and body image as a result of mastectomy and subsequent reconstructive surgeries. Design A systematic review of qualitative and mixed‐methods studies. Data sources Ovid, EBSCOhost, Web of science, SCOPUS and ASSIA ProQuest databases were searched using 1) truncations of breast cancer, hereditary breast cancer and BRCA 2) words relating to partner relationships; spouse, husband, partner, men and couple 3) breast cancer surgeries; mastectomy, prophylactic mastectomy and breast reconstruction and 4) body image. Review method Methodological rigour was quality assessed. Results A total of 756 citations were retrieved. Seventeen articles remained following the removal of duplicates, papers unrelated to breast cancer, male breast cancer, papers that excluded men's experiences of their partner's breast cancer and altered body image. Thematic analysis was applied and produced five themes: experiences of the altered body, communication, impact on relationship, information giving and recommendations. Conclusion Men indicated that perceptions of their partner's altered physique and body image, following mastectomy, was secondary to their health. Some men were distressed by their partner's bodily alterations leading to highly complex and emotive coping mechanisms. Men found talking to their partner about physique and body image challenging. Closed communication, however, often led to conflict and poor psychological well‐being in both partners. To help prepare for the changes to their partner's body, men desired tailored information. Effective information giving contributes to effective coping strategies helping men to better support their partner affected or at risk from breast cancer, leading to enhanced psychological and emotional well‐being in couples. Copyright © 2014 John Wiley & Sons, Ltd.